Present but Useless: Why Power and Culture Create Structural Silence in the Cockpit - Guo, Chengyao; Yang, Yuqian (Journal of Cultural Analysis and Social Change, 2026)
Aviation accident reports often involve human error but overlook the power and cultural factors that control cockpit communication. This study introduced the concept of structural silence. This is a systemic problem in which speech is held back or, more dangerously, spoken in a way that is functionally useless. This helps explain why pilots, even in deadly emergencies, fail to challenge captains. Using cockpit voice recorder (CVR) transcripts from major crashes, this study analysed how the two forces work together. The first is Foucault’s disciplinary power, which we analyse in its two distinct forms: the direct hierarchical power of a present superior and the panoptic power of unseen surveillance. The second is Hall’s high- and low-context cultural model, which directly sets the social cost of speaking. The findings show that this disciplinary fear is often amplified by high-context cultural rules, leading to softened warnings that fail. The analysis also shows that a captain’s direct hierarchical power alone can create silence, even in a low-context culture. This suggests that silence is not a personal failure but a systemic product of power. The study concludes that crew resource management (CRM) training must be culturally aware and must train captains in safety listening, not just training copilots to speak up.